Numerical model of surface morphology and solid-liquid contact angle in wire electrical discharge machining - Zhi Chen; Yifei Zhou; Zefeng Yang; Zhizhong Zhang; Jian Li; Guojun Zhang; Fenglin Han (Journal of Materials Research and Technology)
The workpiece surface after wire electrical discharge machining (WEDM) will naturally leave a large number of micro- or sub-micron level discharge pits/protrusions, which will change the solid-liquid contact characteristics, and can be favorable conditions for the formation of hydrophobic surfaces. However, what kind of surface morphology should be prepared and how to control the discharge process parameters to obtain the maximum solid-liquid intrinsic contact angle has not been systematically studied yet, which makes it difficult to stably and controllably prepare hydrophobic surfaces with large contact angles. This study proposes an evaluating method for the surface morphology based on surface roughness and fractal dimension in WEDM. The numerical model between surface morphology feature and contact angle is established. Through optimizing the discharge process parameters, a set of discharge process parameter combinations for the maximum solid-liquid contact angle has been obtained. The experimental results indicate that, compared to the machined surface after precision grinding, the surface morphology with anisotropic discharge pits/protrusions can transform hydrophilic surfaces (contact angle 88.1°) into hydrophobic surfaces (contact angle 125.5°). The contact angle of the surface machined by WEDM does not increase with the increase of surface roughness. When establishing the numerical models of surface morphology and contact angle, it is necessary to consider both surface roughness and fractal dimension simultaneously. The established numerical model has been experimentally verified to have high prediction accuracy (the relative error less than 4%). Combining the established numerical model and multi-objective optimization algorithm, the contact angle of the surface machined by WEDM is greater than 125°, and the stability and controllability of hydrophobic surface preparation are greatly improved. The numerical model established in this study can guide the selection of discharge process parameters and the preparation of surface morphology for adjusting solid-liquid contact characteristics in WEDM.